2017
DOI: 10.1055/s-0037-1615794
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Neonatal Lumbar Punctures: Experience at a Large Pediatric Tertiary Care Center in Canada

Abstract: Nearly half of all CSF samples in the study period were contaminated. Traumatic samples were more common in younger neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
2
4
1
Order By: Relevance
“…This result was the same regardless of the RBC count in the five LPs for which the CSF RBC count was not verified. Although previous reports have shown that older age was related to LP success in this age group [ 10 , 16 ], the present study found no significant association between age and LP success. This finding may be due to the relatively smaller population in our study than in the previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…This result was the same regardless of the RBC count in the five LPs for which the CSF RBC count was not verified. Although previous reports have shown that older age was related to LP success in this age group [ 10 , 16 ], the present study found no significant association between age and LP success. This finding may be due to the relatively smaller population in our study than in the previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…8 These differences and possible selection bias are likely to explain these discordant age-specific incidences. Collating the present and previous findings, 7,13 at least 4 out of 10 neonatal LPs are traumatic to the extent of being visually contaminated by blood.…”
Section: Discussionsupporting
confidence: 79%
“…Without proper sedation, these small patients are inclined to struggle during the procedure, increasing the risk of failed sampling and tissue trauma caused by the spinal needle. Traumatic lumbar punctures (TLPs), defined as a specified count of red blood cells in the CSF sample, are frequent in neonates and infants, [6][7][8][9][10][11][12][13][14][15] affecting 27 to 55% of LPs using 400 to 500 erythrocytes/µL of CSF as a criterion of TLP. [6][7][8]11,13,14 These criteria may vary much between studies from low counts of erythrocytes up to even 10,000 erythrocytes/µL.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 ] The incidence of traumatic CSF taps in children ranges from 12% to 26% in studies and can be as high as 47.7% amongst neonates. [ 5 6 ] These are affected by the experience of the performer as well as the age and position of the child. Younger neonates tend to have more traumatic punctures due to procedural difficulties.…”
Section: Discussionmentioning
confidence: 99%